Comparative study of phraseological units with color components in the German and Uzbek languages - Jurayeva, Yulduz (The Lingua Spectrum, 2025)
This article is devoted to a comparative study of phraseological units with a color component in the German and Uzbek languages. The main aim of the research is to identify similarities and differences in the semantic structure, imagery, and cultural symbolism of color designations, which play an important role in the linguistic worldview of both nations. Color components traditionally reflect not only visual characteristics of objects but also profound cultural, historical, and emotional meanings that shape the worldview of a people. The study analyzes the most widespread phraseological units with the colors weiß, schwarz, rot, grün, and blau in German and their functional equivalents in Uzbek – oq, qora, qizil, yashil, and ko‘k. The comparative analysis shows that despite the existence of universal associations such as “white – purity,” “black – evil,” or “red – danger,” each culture assigns its own national nuances to these colors, influenced by traditions, mythology, and social values. For example, the Uzbek language uses the positive symbolism of the color ko‘k more widely, while German actively employs blau in figurative meanings. The findings deepen the understanding of linguistic specificity and may be useful in teaching, translation studies, and intercultural communication.